Kesadaran Masyarakat Dalam Menggunakan Media Sosial Untuk Menghindari Terjadinya Modus Penipuan Online - Novaldo Nur Firmansyah; Zatiahtun Nufus; Reza Mauldy Raharja (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
This research aims to increase public awareness regarding how to avoid threats that often occur in society, especially online fraud which is currently on the rise, it is important to understand that online fraud crimes are a serious threat to society in the current digital era. The negative impact of the development of information technology, especially on social media, has led to an increase in online crime cases. In this discussion, the large number of crime victims is caused by low awareness in society. This crime has detrimental social and economic impacts on its victims. Including financial and psychological losses that disturb the victim's mental health. Therefore, appropriate steps are needed to increase public awareness of the risks of online fraud tactics.